Sosialisasi Pendidikan Anti Korupsi Sikap Disiplin pada Anak yang Ketergantungan Gadget Melalui Permainan Lego - Eka Selvi Handayani; Agustinus Bernadinus Pati; Maria Clarita; Uswatun Khasanah; Ester Tabita; Widya Nanda; Irene Avrilia Nirmala (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2026)
corruption is a serious issue that must be addressed from an early age through character education. Children who are overly dependent on gadgets tend to experience a decline in discipline and moral values. Therefore, a socialization program on anti-corruption education using a creative method through LEGO play was organized, entitled "Socialization of Anti-Corruption Education and Discipline Attitudes in Children with Gadget Dependency through LEGO Play at SD Negeri 004 Samarinda Ilir, Grade V, Gg Budiman, Jl. Lumba-Lumba, Selili, Samarinda.".The purpose of this activity is to instill the principles of honesty, responsibility, and to foster disciplined behavior among students in a fun and interactive way. The method used is collaborative, where children are encouraged to build structures using LEGO bricks while being taught about anti-corruption principles.The results of this activity show a positive development in student behavior, with a noticeable reduction in gadget dependency and an increased understanding of the importance of honesty and discipline. This program serves as an effective learning approach to instill character values contextually and enjoyably within the elementary school environment.